Physical Properties Investigation on Sunscreens with Colloidal Gold and Moringa oleifera Extract - Ruth Febriana Kesuma; Eva Monica; Rokiy Alfanaar (Chemistry Department, The University of Brawijaya, 2020)
Botanicals were known as active ingredients in sunscreens due to their dermal protecting. Gold in colloidal form has a completely unique property for the reason that it may be used as photoaging material. The exposure of UV radiation to skin can cause erythema and skin cancer. The aim of this study was to determine the physical properties of the sunscreens made from Au/ZnO and antioxidant from Moringa oleifera extract such as the sun protection factor (SPF), pH, spreadability, and adhesion. The Moringa oleifera were extracted by maceration. Maceration with 70% ethanol of dried leaves exhibited DPPH scavenging activity (EC50 235.01 μg/mL). Diffuse reflectance UV-Vis spectra of ZnO and Au/ZnO revealed absorption at λex of 385 nm which were equivalent to a bandgap energy of 3.22 eV. Au/ZnO posed a localized state at λex of 385 (3.65 eV). The sunscreens with formulations F1, F2, F3, and F4 showed high SPF number of 20.1479, 21.0008, 22.3872, and18.4631. Kruskal-Wallis test showed significant differences between sunscreen formulations.